Youths and poor emotional wellbeing: is it just a matter of stress? A longitudinal survey (Swiss Medical Weekly, 2020)
WHAT IS KNOWN ON THE SUBJECT: To date, research on emotional wellbeing among youths has been mostly based on cross-sectional studies, and little is known about its evolution over time.WHAT DOES THIS ARTICLE ADD: Our study adds a longitudinal approach to emotional wellbeing and defines different groups of youths according to their evolution over a two-year period. Stress and perceived health status seem to be the most important factors related to emotional wellbeing. Our research shows the importance of health care professionals exploring psychological health, especially when a youth has atypical somatic complaints. This could allow the early detection of psychological problems and the provision of proper timely treatment.AIM OF THE STUDYTo assess how emotional wellbeing evolves over a two-year period among youths in Switzerland, and to assess their characteristics.METHODSData were obtained from the first and third waves of the GenerationFRee study (n = 1311, aged 15–24 at baseline). The sample was divided into four groups according to the evolution of their emotional wellbeing (WB): good at both waves (GoodWB: 67.9%), poor at T1 and good at T3 (BetterWB: 8.4%), good at T1 and poor at T3 (WorseWB: 13.2%), or poor at both waves (PoorWB: 10.4%). Significant variables at the bivariate level were included in a multinomial regression analysis using GoodWB as the reference category. Results are given as relative risk ratios (RRRs).RESULTSThe BetterWB group reported more stress at T1 (RRR 1.34), as did the WorseWB group at T3 (1.43). Those in the WorseWB group were more likely to report poorer health status at T3 (6.51). Finally, the PoorWB group reported more stress at T1 (1.33) and T3 (1.44), and poorer health status at T1 (9.39) and T3 (5.75). Other variables not significant in all groups were perceived onset of puberty, having a chronic condition, area of residence and relationships with parents.CONCLUSIONUsing a longitudinal approach, stress and perceived health status seem to be the main factors that change with emotional wellbeing among youths. Inquiring about stress could be a good proxy for emotional wellbeing, especially among males, who tend to underestimate their emotional worries.